Properties of Human Tissue Thromboplastins from Brain, Lung, Arteries, and Placenta - Gonmori, H; Takeda, Y (Thrombosis and Haemostasis, 1976)
Properties of purified and delipidated human tissue thromboplastins (TTPs) from brain (BTTP), lung (LTTP), arteries (ATTP) and placenta (PTTP) were studied. The extinction coefficients were closely similar with a mean value of 8.3 ± 0.01 (SD). The molecular weights were 200,000 ± 3,000 (SD) (BTTP), 90,000 ± 2,000 (SD) (LTTP), 110,000 ± 3,000 (SD) (ATTP) and 250,000 ± 4,000 (SD) (PTTP). The maximum activity of each delipidated TTP after relipidation was obtained when phospholipid-delipidated TTP ratio was 2.0, and the maximum specific activity was 440 units per mg BTTP, 270 units per mg LTTP, 80 units per mg ATTP and 600 units per mg PTTP. Ouchterlony analysis with anti-delipidated PTTP antibody showed the reaction of partial identity between delipidated TTPs and the antibody. Studies of the reactivity of I-125-delipidated TTPs with the antibody gave the following average values for % bound I-125-TTPs in 2 hours: 3.6± 0.2 (SD) % (I-125-BTTP), 11.0± 0.3 (SD) % (I-125-LTTP), 4.4±0.2 (SD) % (I-125-ATTP) and 13.7±0.3 (SD) % (I-125-PTTP). It was also found that the antibody markedly neutralized the coagulant activity of saline extracts of brain, lung and placenta. These results indicate that delipidated BTTP, LTTP, ATTP and PTTP are different while being similar in some aspects and that complete TTPs are not coated with lipids in a manner inaccessible to anti-delipidated PTTP antibody.